2018
DOI: 10.1002/pat.4247
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer nanocarriers for recognition and sustained release of diclofenac

Abstract: In this study, a series of imprinted poly(methacrylic acid-co-ethylene glycol dimethacrylate) nanocarriers for diclofenac and corresponding nonimprinted polymer nanocarriers have been synthesized in 4 different types of solvents by precipitation polymerization. The products were characterized by Fourier transform infrared, scanning electron microscopy, dynamic light scattering, and Brunauer-Emmett-Teller measurement. Results showed that uniformly sized molecularly imprinted polymer (MIP) nanospheres with relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Once the critical mass is reached, the polymer is no longer solubilized and precipitates as spherical particles. In this way, the size and the porosity of the spherical particles are easily controlled by choosing the appropriate reaction mixture [95], but with the possibility that the monomer and the template could be irreversibly solubilized causing a partial loss of the reagents and hence a decrease of the polymerization yield [96]. Another option is represented by the emulsion polymerization in which two immiscible solvents are used in the presence of a stabilizing surfactant to obtain small droplets (micelles) inside which the polymerization reaction takes place [97].…”
Section: Type Of Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Once the critical mass is reached, the polymer is no longer solubilized and precipitates as spherical particles. In this way, the size and the porosity of the spherical particles are easily controlled by choosing the appropriate reaction mixture [95], but with the possibility that the monomer and the template could be irreversibly solubilized causing a partial loss of the reagents and hence a decrease of the polymerization yield [96]. Another option is represented by the emulsion polymerization in which two immiscible solvents are used in the presence of a stabilizing surfactant to obtain small droplets (micelles) inside which the polymerization reaction takes place [97].…”
Section: Type Of Synthesismentioning
confidence: 99%
“…In addition to the factors affecting the solubility of the monomers and templates in the chosen solvent, also the selectivity of the monomers towards the CECs has to be taken into account. For example, methacrylic acid [95] and 2-vinyl pyridine [65] were used in similar synthesis, through precipitation polymerization, for the selective removal of diclofenac but, due to the different chemical interactions between the monomers and the diclofenac, the two obtained polymers exhibited different adsorption efficiencies, around 65 mg/g and 350 mg/g, respectively. Another example is given by Huang et al [108], who described the synthesis of two different MIPs for the selective extraction of quercetin, through bulk polymerization using two monomers, 4-vinylpirydine (MIP-4VP) and acrylamide (MIP-AM).…”
Section: Solvents Monomers and Water Compatibilitymentioning
confidence: 99%
“…In this way, Drug Loading Content (DLC) and Drug Loading Efficiency (DLE) were determined according to Equations In vitro release studies were carried out in phosphate buffer at pH 7.4 (10 −3 M) according to the dialysis bag diffusion technique [23]. For this purpose, 20 mg of SUT loaded particles were immersed in 1 mL of PBS and placed in a dialysis tube, which was sealed at each end with clamps.…”
Section: Drug Loading Procedures and In Vitro Release Studiesmentioning
confidence: 99%
“…Equation 14is used successfully for the analysis of the first 60% of the release profiles [38]. In order to explore the kinetics of the in vitro drug release and to understand the mechanism of the release process from the prepared device, different kinetic models, such as zero-order, first-order, Higuchi, and Ritger-Peppas, were applied according to the following Equations (12-15, respectively) [23]:…”
Section: In Vitro Release Studiesmentioning
confidence: 99%
“…The results showed good morphology, monodispersity, and high adsorption capacity and excellent selectivity to the target molecule, metronidazole. Zeng et al (2018) 11 also imprinted poly(methacrylic acid-co-ethylene glycol dimethacrylate) nanocarriers for recognition and sustained release of diclofenac in four different types of solvents. Results showed that uniformly sized nanospheres with relatively good porosity could only be obtained in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%